Biodiversity, communities, and climate change - Kala, C. P.; Silori, Chandra Shekhar; Energy and Resources Institute (2013)
With reference to India.
Includes bibliographical references and index.
Keywords: Biodiversity conservation -- India -- Uttarakhand; Forest reserves -- India -- Uttarakhand; Medicinal plants -- India -- Uttarakhand; Plant diversity conservation -- India -- Uttarakhand; Climatic changes -- India -- Uttarakhand; Biodiversity -- Climatic factors -- India -- Uttarakhand; Climate change mitigation -- India -- Uttarakhand; Biodiversity conservation -- Economic aspects -- India -- Uttarakhand; Biodiversity conservation -- Government policy -- India -- Uttarakhand